Managing Director's Global Policy Agenda to the International Monetary and Financial Committee. (Policy Papers; Policy Paper, 2015)
The Executive Summary is also available in: Arabic , Chinese, French, Japanese, Russian, and Spanish. The membership is facing a rapidly changing and uncertain world. The United States is poised to raise interest rates amid ongoing recovery, China's expected slowdown as it rebalances growth is creating larger-than-anticipated spillovers, and commodity producers are facing the end of a long cycle of high commodity prices. These necessary transitions pose challenges, particularly for emerging and low-income developing countries, where prospects have dwindled the most. Policymakers are increasingly grappling with difficult policy trade-offs. Faced with limited room to maneuver and the need to adapt to new realities, what relative weight should be placed on supporting demand and current activity, on reducing financial risks as financial conditions tighten, and on implementing urgently needed structural reforms to revive future growth? Policies need to reflect country circumstances and coalesce into a new multilateralism. Mutually reinforcing policies are needed to support growth today, invest in resilience and safeguard financial stability, and implement the structural reforms needed for a sustainable and inclusive future. Policies should reflect member circumstances and also add up to a coherent whole-to ensure that demand is created not substituted, market resilience is enhanced not circumvented, and that structural reforms are enacted not delayed. Cooperation is vital in areas such as the global financial safety net, trade, climate change, international taxation, sustainable development goals (SDGs), and demographic transitions and migration. The Fund will support the membership at this juncture. The Fund has both the universal membership and mandate to address growth and economic stability issues at the national and global levels. To support the membership most effectively, the Fund will focus on three priorities that best reflect this new AIM: -- Agility. Advice will focus on policies to support members cope with evolving transitions-respond to tighter and more volatile financial conditions and implement effective macro-structural reforms. The lending framework will deliver financial assistance quickly where needed. Delivery of technical assistance and training will be enhanced by greater use of online tools. -- Integration. In the face of growing policy trade-offs, the Fund will support its members by better integrating policy advice across sectors, embracing evolving priorities, promoting integration of global, regional, and bilateral safety nets, and better leveraging synergies between surveillance and capacity building. -- Member-Focused. With policy concerns evolving rapidly and advice becoming more dependent on country-specifics, the Fund will deepen its engagement with members, better deliver its knowledge, and ensure faster feedback to policymakers. The Fund continues to refine its core work-surveillance, lending, and capacity building-and to attain greater intellectual and cultural diversity to respond to this changing global environment and its corresponding policy challenges. To further improve services to the membership, Fund activities need to be fully supported by adequate financial, human, budgetary, and technological resources.